In-vitro antibacterial activity of the seed extract of three member Artocarpus towards methicillin resistant Staphylococcus aureus (MRSA) - Prastiyanto, Muhammad Evy; Azizah, Inas Hasna; Haqi, Hafizha Dara; Yulianto, Bagus Dwi; Agmala, Aulia Bella; Radipasari, Zhafira Dias; Astuti, Nita Ayu Dwi; Putri, Arifani Rahma (Jurnal Teknologi Laboratorium, 2020)
Methicillin-Resistant Staphylococcus aureus (MRSA) infections have created a critical need for the development of natural antibacterials from biological sources. This research aimed to investigate the antibacterial activity of the seed extract of three-member Artocarpus (Artocarpus heterophyllus, A. champeden and A. camansi) against MRSA which are the most prevalent causes of infections in patients. Crude seed extracts of three-member Artocarpus were evaluated for their antibacterial activity against MRSA. The antibacterial activity against MRSA of the three extracts was assayed in vitro by the agar well diffusion assay and agar microdilution method (Minimum inhibitory concentration [MIC] and Minimum bactericidal concentration [MBC]). The best antibacterial activity, calculated as a zone of inhibition and MIC, MBC values. The Crude seed extracts of three-member Artocarpus showed antibacterial activity against the MRSA in the agar well diffusion assay (1.5-9 mm inhibition diameter). The MIC value of extract showed at 15.62 mg/mL and the MBC value of seed extract of A. heterophyllus at 62.5 mg/mL, A. champeden at 31.25 mg/mL, A. camansi at 250 mg/mL. The data have revealed that all seed extracts have the potential to be developed as antibacterial agents, particularly against MRSA strain. Further in vivo research and discovery of mode action are needed to shed light on their antibacterial effects. Research on anti-MRSA of seed extract of Artocarpus against MRSA has not been reported. Studies on the antibacterial activity against MRSA can provide new information about the benefits seed of members of Artocarpus as a source of natural antibacterial.